Satellite Observations Reveal Declining Diatom Concentrations in the Three Gorges Reservoir: The Impacts of Dam Construction and Local Climate - Menglan Gan; Lei Feng; Jingan Shao; Li Feng; Yao Wang; Meiling Liu; Ling Wu; Botian Zhou (Remote Sensing)
An effective satellite observation system is developed to retrieve the diatom concentration in freshwater ecosystems that could be utilized for understanding aquatic biogeochemical cycles. Although the singular value decomposition-based retrieval model can reflect the complicated diatom dynamics, the spatial distribution and temporal trend in diatom concentration on a large scale, as well as its driving mechanism, remain prevalently elusive. Based on the Google Earth Engine platform, this study uses Sentinel-2 MultiSpectral Instrument imagery to track the comprehensive diatom dynamics in a large reservoir, i.e., the Three Gorges Reservoir, in China during the years 2019–2023. The results indicate that a synchronous diatom distribution is found between the upstream and downstream artificial lakes along the primary tributary in the Three Gorges Reservoir, and the causal relationships between the declining diatom trend and hydrological/meteorological drivers on the monthly and yearly scales are highlighted. Moreover, the Sentinel-derived diatom concentration can be used to ascertain whether the dominant algae are harmful during bloom periods and aid in distinguishing algal blooms from ship oil spills. This study is a significant step forward in tracking the diatom dynamics in a large-scale freshwater ecosystem involving complex coupling drivers.